Competition and Audit Fees. - Maher, Michael W.; Tiessen, Peter (The Accounting Review, 1992)
Presents a study to determine whether real audit fees decreased between 1977 and 1981. Behavior of audit fees during a period of apparent increasing competition in the market for independent audit services; Method of study; Claims of increasing fee competition in the market for independent audit services.